Regular perturbation on the group-velocity dispersion parameter for nonlinear fibre-optical communications - Vinícius Oliari (Nature Portfolio, 2020)
Nonlinear effects have been studied in optical fiber communications channels under various specified parameter regimes. Here, the authors develop an approximate model via perturbation that is more accurate for the highly nonlinear regime.